Analysis of audiovisual resources and their effects in the development of auditory skills in the english learning in kindergarten children at Medalla Milagrosa Elementary School - Estrada, Daisy (UDELAS, 2011)
The final project consolidades much of the knowledge acquired during the academic stage, therefore, it si a fundamental requirement to pursue a degree. It forms a kely pilar in achieving a goal and it is also a formal proposal of the suthoers to contribue to society, in this case, with a descriptive study.